MAKNA TRADISI MAPPETTU ADA DALAM PERNIKAHAN ADAT BUGIS DI KELURAHAN BENTENG - Jais, Ahmad; Noor Efni Salam; Nurjanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT This study examines the meaning of the mappettu ada tradition in Bugis traditional marriage in Benteng Village, Sungai Batang District, Indragiri Hilir Regency. Mappettu ada is a crucial stage that involves discussions between families about various aspects of marriage, including sompa (dowry) and dui mendre (expenses). Using a qualitative descriptive method, data were collected through interviews, observations, and documentation. The results show that mappettu ada symbolizes commitment, respect, and consensus in Bugis culture. This tradition strengthens family ties and preserves cultural heritage. Keywords: Mappettu ada, Symbolic Meaning, Cultural Values, Bugis Traditional